Hubungan Tanggung Jawab Guru terhadap Kedisiplinan Guru Kelas dalam Mengajar - Fitri Yani (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2021)
The purpose of this study was to determine the relationship of teachers' responsibility to classroom teachers' discipline. This type of research was quantitative correlational research. The population was six teachers at the State Elementary School of 012 Parit 7 Sungai Pinggan, Batang Tuaka District. The data in this study were collected using questionnaires and documentation techniques. Furthermore, the collected data was analyzed using the Product Moment Correlation formula. The results of the study indicated that there was a positive, and significant relationship between teachers' responsibility and classroom teachers' discipline. Through data analysis on the two variables, the output of the correlation coefficient was 0.582, meaning that the level of strength of the relationship between the teachers' responsibility and teachers' discipline was 0.582 or moderately strong. It means that the relationship (correlation) was significant at a significance value of 0.05. Thus, there was a positive and significant relationship between the teachers' responsibility to the classroom teachers' discipline in teaching.